Peningkatan Pengetahuan Dan Keterampilan Masyarakat Dalam Penanganan Pertama Luka Bakar Di Kelurahan Mangga Dua Selatan Kecamatan Sawah Besar - Hardin La Ramba; Yarwin Yari; Enni Juliani (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Burns are damage to the body's skin caused by heat trauma or cold trauma (frost bite). The community does not have optimal knowledge about burns, therefore the community does not have optimal knowledge about the first treatment of burns and the community does not have good skills in the first treatment of burns. The purpose of this community service is to provide knowledge about burns, burn first handlers and provide training on first handlers of burns first handlers. The methods used are burn treatment, counseling on the first treatment of burns and training on burn management. The number of respondents was 15 people. From the results of the pretest conducted, it was found that the average respondent had less knowledge and skills in handling burns. Evidenced by the average value of repondents below 7, and only one respondent has a value of 7 which means that they have less knowledge in handling burns. This is likely because respondents already know little about burns. After respondents were given knowledge about burn management, as well as demonstrations related to burn management, there was an increase in knowledge in burn management, although some have not achieved scores in the good category, but all have shown increased knowledge and skills in burn management.